Perceptions of gender norms and sex-typed cognitive abilities among Indian adolescents – A study of Andhra Pradesh and Telangana. (April 2022) - Das, Sumit Kumar; Mishra, Udaya S.; Das, Milan; Das, Pritilata
Highlights: Females were more supportive of an egalitarian society, whilst males were more supportive of masculinity in society. Boys outperformed girls in quantitative aptitude and receptive vocabulary when other factors were controlled. Adolescents' power trait had significant bearing on quantitative, receptive and reading skills of cognitive abilities. A focus on supporting high-quality girl education while avoiding gender stereotypes in the society is required. Abstract: Adolescents' sex-typed cognitive ability is said to be shaped by gender norms and gender roles. Gender discrimination is displayed in every sphere given the persistence of conservative societal values in India. This study used data from the most recent round of the Young Lives survey to investigate the impact of gender norms and gender stereotypes on sex-typed cognitive abilities in quantitative aptitude, receptive vocabulary, and reading ability among Indian adolescents living in the state of Andhra Pradesh and Telangana. As regards perception of gender norms, girls were more in favour of egalitarian society as against boys in favour of masculinity in the society. Boys outperformed girls in quantitative aptitude and receptive vocabulary when the effect of gender stereotypes and other socio-demographic influences on sex-typed cognitive abilities were controlled. Wealth status of household, educational qualification, medium of instruction and the perception of masculinity were found to have significant bearing on all three types of cognitive ability. Such a difference in cognitive abilities favouring boys call for an emphasis on promoting girls' education in terms of quality and avoiding gender stereotype in the educational environment.